Smoking and oral and pharyngeal cancer: a meta-analysis - Possenti, Irene; Miotti, Stefano; Gallus, Silvano; Bagnardi, Vincenzo; Garavello, Werner; Specchia, Claudia; Smits, Luc; Odone, Anna; Lugo, Alessandra (Oncology Reviews, 2026)
IntroductionOral cavity and pharyngeal cancer (OPC) affects over 580,000 people globally each year, with tobacco and alcohol being key risk factors. This meta-analysis quantifies the excess risk of OPC associated with cigarette smoking and its patterns.MethodsWe carried out a systematic review and meta-analysis of case-control and cohort studies assessing the association between cigarette smoking and OPC risk, including articles published up to February 2025. Using a combined umbrella and traditional review approach, we estimated pooled relative risks (RR) by smoking status, intensity, duration, and time since quitting.ResultsOut of 137 eligible articles, 115 original studies were included in this meta-analysis. Relative to never smokers, the pooled risk of OPC was 3.58 (95% CI: 3.03–4.24; n = 54) among current smokers, 1.61 (95% CI: 1.44–1.81; n = 53) among former smokers, and 2.45 (95% CI: 2.19–2.75; n = 80) among ever smokers. Subsite-specific analyses showed RRs of 3.39 (95% CI: 2.64–4.35; n = 25) for oral cancer and 4.24 (95% CI: 2.96–6.09; n = 18) for pharyngeal cancer in current versus never smokers. Risk rose steeply with both smoking intensity and duration, doubling after 6 cigarettes per day or 7 years of smoking, before reaching a plateau around an RR of 5 at 20 cigarettes per day or 20 years. The risk declined linearly with longer time since quitting, with a 50% reduction observed within 10 years of cessation.ConclusionOur findings reaffirm the substantial impact of smoking on OPC risk and stress the need for efforts to avoid smoking initiation and support cessation.